Nivel de satisfacion en los usuarios de la compañía de transporte escolar e institucional Riveras del Babahoyo S.A. - Benitez Contreras, Kevin Eduardo (2019)
The objective of this Case Study is to publicize the level of satisfaction of the users of the Riveras del Babahoyo School and Institutional Transport Company, the type of method used is the inductive one because we analyze the cases of disagreement by the users of the company, for this it is necessary to have contributions from bibliographic links that help to support what is desired to manifest in this work, through the surveys we can verify that the users consider the service of the company to be unsatisfactory because of the which company decreases its productivity The company needs to have a better administration, also train the drivers of the transport units so that they can perform a quality service